2018
DOI: 10.5433/1679-0359.2018v39n1p221
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of cysticercose in relation to hydrographic net at triangulo mineiro, MG, Brazil

Abstract: Cysticercosis affects cattle, which develop the larva of Taenia saginata after ingesting their eggs, which are released by humans. It is a parasite that is distributed worldwide. The use of geoprocessing allows a better definition of endemic areas and populations that face different levels of risk and thus creates a basis for specific control programs for each farming system. The objective of this study was to evaluate the epidemiological situation of bovine cysticercosis in four municipalities in the Triângul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As egg survival is determined by humidity, eggs are able to survive in water for a long time. Furthermore, several articles pinpointed access to surface water or the proximity of a wastewater treatment plant as risk factors for cysticercosis [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As egg survival is determined by humidity, eggs are able to survive in water for a long time. Furthermore, several articles pinpointed access to surface water or the proximity of a wastewater treatment plant as risk factors for cysticercosis [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Boone et al [62] reported that the flooding of pastures, free access of cattle to surface water and proximity of wastewater effluent were explanatory variables for bovine cysticercosis in Belgium. In Brazil, the water source from rivers or streams was determined to be the main risk factor for bovine cysticercosis in multiple farms [63]. The flooding of agricultural land and grassland has also been associated with human and porcine cysticercosis in Kenya [64].…”
Section: Sewage Treatment and Surface Watermentioning
confidence: 99%
“…In Brazil, beef cattle are raised mostly extensive [76], where cattle feeding occurs in large areas of pastures with free access to uncontrolled water sources. The relation with access to contaminated water has been described by several authors in Brazil, detailing risks such as the free access of cattle to uncontrolled water sources [7], the presence of flooded pastures [27] or areas with a high rainfall index [23], proximity to rivers and their tributaries that fed municipalities [47], and poor quality of water [37]. Similar risk factors have been reported in other countries, such as the access to risky water sources with sewage treatment effluent plant in proximity [77], the flooding of pastures and free access to surface water, Access of cattle to non-controlled water sources and sport fishing activities near the farms States of São Paulo, Minas Gerais, Mato Grosso and Mato Grosso do Sul Case-control study in farms based on post-mortem data Rossi et al [7] Animal purchasing and presence of flooded pastures Paraíba State Logistic regression of results obtained for herd-level using serological analyses…”
Section: Epidemiologymentioning
confidence: 99%
“…Case-control study in farms Acevedo-Nieto et al [61] Interference of the rivers and their tributaries that fed the municipalities Triangulo Mineiro, Minas Gerais, Risk analysis along with mapping and spatial analysis of data Duarte et al [47] Raising animals in regions with large human population, percentage or urban houses and rural areas with inappropriate sewage system and the proximity of wastewater effluent [78]. Water supply for animals appears to be the most frequent route of infection for animals in Spain [79].…”
Section: Colatina Espírito Santomentioning
confidence: 99%
“…. Assim, a utilização do georreferenciamento poderá facilitar a adoção de medidas sanitárias para controle e redução do impacto do complexo teníase cisticercose (Rossi et al, 2016;Duarte et al, 2018). ; ASSANA, E.; NGUEKAM, J. P.; DORNY, P.; BRANDT, J.; GEERTS, S. Regional status, epidemiology and impact of Taenia solium cysticercosis in Western and Central Africa.…”
Section: Georreferenciamentounclassified